Hypothetical model of disease course of COVID-19 patients and their exit plan (Journal of Patan Academy of Health Sciences, 2020)
In view of preparing ourselves for the possible rise of Corona Virus Disease (COVID-19) cases, we have proposed a hypothetical model of disease course in COVID-19 patients admitted in Patan Hospital and the exit plan based on available evidences. This will give us a scientific basis of planning discharge of our future cases. According to it, patients are subjected to repeat Polymerase chain reaction (PCR) on day 20 of illness onset and then every 4 days till negative result. Patients with two negative PCR test repeated 24 hours apart are discharged and advised for 14 days’ home quarantine.